Time to make some noise about a quiet revolution. (9th April 2022) - Calvert, Katrina; Leathersich, Sebastian; Howat, Paul; Van Der Wal, Sarah
Abstract : 'Tomorrow belongs to those who can hear it coming' David Bowie. Language is a living entity that moves and changes. Use of gender‐neutral language in medical literature is increasingly common. It is time for obstetricians and gynaecologists in Australia and New Zealand to interrogate their own bias and desire to maintain the status quo, and to consider reasons for change.